Cytokine-Mediated Regulation of Plasma Cell Generation: IL-21 Takes Center Stage - Tangye, Stuart G. (Frontiers in Immunology, 2014)
During our life we are surrounded by continuous threats from a diverse range of invading pathogens. Our immune system has evolved multiple mechanisms to efficiently deal with these threats to prevent them causing disease. Differentiation of mature B cells into plasma cells (PC) - the antibody (Ab) secreting cells of the immune system - is critical for the generation of protective and long-lived humoral immune responses. Indeed, efficient production of antigen (Ag)-specific Ab underlies the success of most currently available vaccines. The mature B cell pool is composed of several subsets, distinguished from one according to size, surface marker expression, location and Ag exposure, and they all have the capacity to differentiate into PCs. For a B cell to acquire the capacity to produce Abs, it must undergo an extensive differentiation process driven by changes in gene expression. Two broad categories of Ag exist that cause B cell activation and differentiation: T cell dependent (TD) or T cell independent (TI). In addition to the B cell subset and nature of the Ag, it is important to consider the cytokine environment that also influences how B cell differentiation is achieved. Thus, while many cytokines can induce Ab secretion by B cells after activation with mimics of TD and TI stimuli in vitro, they can have different efficacies and specificities, and can often preferentially induce production of one Ig isotype over another. Here, we will provide an overview of in vitro studies (mouse and human origin) that evaluated the role the different cytokines in inducing the differentiation of distinct B cell subsets to the PC lineage. We will place particular emphasis on IL-21, which has emerged as the most potent inducer of terminal B cell differentiation in humans. We will also focus on the role of IL-21 and defects in B-cell function and how these contribute to human immunopathologies such as primary immunodeficiencies and B-cell mediated autoimmune conditions.